AMP-Student: Challenges for Scientific Publishing - Pedro Câmara Pestana; Ana Rita Ramalho; Bernardo Marques da Silva; Joana Revés; Mariana Fernandes; Sandra Maurício (Acta Médica Portuguesa, 2016)
N/A